Remarkable improvement in drilling fluid properties with graphitic-carbon nitride for enhanced wellbore stability - Anwar Ahmed; Erum Pervaiz; Iftikhar Ahmed; Tayyaba Noor (Heliyon)
This study examines the viability of using graphitic-Carbon Nitride (g-C3N4) nanomaterial as shale stabilizer drilling fluid additive having applications in the oil and gas wells drilling. Shale stability is important especially when drilling horizontal and extended reach wells with water-based muds (WBM) to tap unconventional reservoirs namely shale oil and shale gas. For this study, the g-C3N4 nanomaterial was produced by melamine pyrolysis, and characterized by X-Ray Diffraction, Scanning Electron Microscopy and Fourier Transform Infrared spectroscopy techniques. The developed g-C3N4 was used to formulate the WBM and its impact on the formulated mud system's rheological and filtration control characteristics as well as on shale stability was examined. In comparison to the base mud, the treated mud showed lower Fluid Loss (FL) and higher thermal stability. FL was reduced by 41.8 % and 68 % under Before Hot Rolling (BHR) and After Hot Rolling (AHR) conditions, respectively, with a maximum cake thickness of 1 mm. The Yield Point was improved by 52 % and 66 % under BHR and AHR conditions, respectively. The increase in Plastic Viscosity, and Apparent Viscosity was 23.8 %, and 38 %, respectively. Shale recovery was 99.6 % in g-C3N4 treated fluid compared to 88 % in the base fluid. The treated shale Brunauer-Emmett-Teller (BET) surface area and the pore volume were significantly reduced compared to the pure shale, indicating significant plugging of shale nano- and micro-pores. The BET surface area of the g-C3N4 treated shale sample was 0.0405 m2/g compared to pure shale sample's surface area 0.3501 m2/g. Correspondingly, the pore volume of treated shale was 0.000029 cm3/g compared to the pure shale sample's pore volume 0.000911 cm3/g. Therefore, based on the experimental results obtained, it is inferred that the developed g-C3N4 nanomaterial has potential applications in WBM systems for drilling long shale sections.